GIS-based identification of groundwater potential zones to explore water sources in Matalom, Leyte, Philippines - Sobrio, Glenda Loraine S.; Jago-on, Karen Ann B. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Access to sufficient water for domestic use remains a challenge despite all the initiatives addressing the gap in water supply. Many households in the Philippines are situated in underserved areas where access to water for their daily needs is limited and difficult. To address this issue, this study examined the current water supply conditions experienced at the household level in Matalom, Leyte, and aimed to tackle the issue by enhancing the water supply delivered to households through a geospatial approach to mapping groundwater.

This study conducted a household survey which revealed that out of the 326 household respondents, 234 (71.75%) were under Level 1 and 2 systems, which highlighted the need to expand the water supply coverage and infrastructure by upgrading to Level 3 systems so that all households have easy access to water in their homes. Furthermore, these households were willing to pay for improved water services as the survey found out that a majority (41.72%) of households consumed an average of 26 to 50 liters per day, which unfortunately, fall below the standards set by the World Health Organization which is at least 100 liters per person per day to meet basic daily needs. It was found that households learned to limit their water use and sought alternative water sources to supplement the lack of water supply.

In response, this study explored potential water sources considering ten key parameters, namely, elevation, slope, land use/land cover, soil type, geology. rainfall, curvature, topographic wetness index, drainage density, and lineament density to map groundwater potential zones using weighted overlay analysis in GIS and AHP methods. The results of the AHP showed that geology (17.1%), rainfall (14.4%), and soil type (12.9%) are the most important parameters contributing to groundwater occurrence, while slope (6.4%) and elevation (5.1%) were the least important.

Thematic maps of each parameter were produced and integrated using weighted overlay analysis to generate the final groundwater potential zone map. The final map revealed low, medium, and high potential zones in the study area, where high potential is dominant, occupying 59.03% of the study area. Low potential zones occupy only a negligible portion of the study area, while the medium and high potential zones cover an area of 51.47 sq. km., and 74.15 sq. km., respectively. Further, 19 validation points consisting of locations of existing jetmatic water pumps, springs, and deep wells were used to verify the accuracy of the resulting map. 10 of which are situated in the medium potential zone, while the other 9 are situated in the high potential. Moreover, a sensitivity analysis was also conducted to test the AHP model in mapping GWPZs.

In conclusion, this study found that the study area, Matalom, Leyte, has groundwater potential zones and the water supply problem experienced by most households might not be caused by the lack of water resources per se but might be attributed to water delivery and infrastructure.

Keywords: water supply, household survey, groundwater mapping, geographic information system, analytical hierarchy process
Thesis
Keywords: Groundwater -- Philippines -- Matalom, Leyte; Geographic information systems -- Philippines -- Matalom, Leyte; Water -- supply -- Philippines -- Matalom, Leyte